The effect health education with audio visual media on the level of knowledge as an effort to prevent pre-eclampsia in pregnant women - Nugraha, Nareswari; Remedina, Gipfel; Nataningtyas, Candra Dewi (International Journal of Nursing and Midwifery Research, 2023)
Pre-eclampsia is a pregnancy-related disease characterized by  hypertension, edema, and proteinuria.  Pregnancy-related  problems  may arise that are caused directly by hypertension. Pregnant women can prevent preeclampsia  by increasing  their understanding  through  health education with  audio-visual   media  to  increase   their  knowledge.   This  research   aims  to determine  the effect of health education  using audio-visual  media on the level  of knowle1dge in  an  effort  to  prevent   pre-eclampsia in  pregnant women. This research uses a pre-experimental design with research  methods  pre-test-post test with one group design. Data collection was carried out usiing a questionnaire. Sampling   method: non-probability sampling by using techniques  A total sample 37 respondents was obtained. The data were analyzed using tests.   Wilcoxonsigned rank. The results  showed  that the level  of knowledge about  pre-eclampsia prevention  before  and  after  health  education was valuable p-value = 0.000, which  means the value of p < 0.05,  then H 1   is accepted,  so it can be concluded  from this  research   that  there  is  an  influence  of  health  education  using  audio-visual media regarding  pre-eclampsia preventive  efforts  on the knowledge  of pregnant  women.